Variety selection and seed quality management in grain legume cultivation - Rubyogo, Jean-Claude; Odhiambo, Wilfred (Burleigh Dodds Science Publishing Limited, 2018)
A key aspect of grain legume crop cultivation is selecting and being able to access the seed of the right type and quality. This is becoming more challenging as grain legumes become cash crops and smallholder farmers transition from subsistence farming to market-oriented production. This chapter discusses the challenges of legume variety selection and seed quality management as well as how they can be addressed, for example through participatory varietal selection (PVS). It includes case studies on improving seed selection and quality management in practice in sub-Saharan Africa.